Pengukuran Kinerja Pengelolaan Zakat Nasional menggunakan Indeks Zakat Nasional (IZN) 2.0 dan Dampaknya terhadap Pengentasan Kemiskinan di Indonesia Periode 2021 - Rini Elvira (Jurnal BAABU AL-ILMI: Ekonomi dan Perbankan Syariah, 2022)
The study aims to measure the performance of national zakat management and its impact on poverty alleviation in Indonesia for the 2021 period. National Zakat Index (N.Z.I.) 2.0, formed based on macro and micro dimensions, is used to measure the performance of national zakat management. The General Poverty Index (GPI), with headcount index, income gap ratio, poverty gap, sen index, and F.G.T. index, and the B.A.Z.N.A.S. Welfare Index (B.W.I.), with indicators of the poverty line, had kifayah. Nisab zakat is used to measure the impact of zakat management on poverty alleviation in Indonesia for the 2021 period. The result show (1) The performance of the national zakat management for the 2021 period is considered very good, with an N.Z.I. value of 0,88. (2) Based on the GPI and B.W.I. indicators, the management of national zakat in the distribution sector has been able to improve the welfare of mustahik and alleviate poverty in Indonesia for the 2021 period